Master class with Amit Peled - Prokofiev, Sergey 1891-1953 (IClassical Academy, 2015)
Israeli cellist Amit Peled, one of the most sought-after pedagogues on his instrument, works with Ferran Albrich on the first movement from Prokofiev's Sinfonia Concertante Op. 125 in a masterclass at the Villa Sandra Lesa. Originally envisioned as a cello concerto and premiered in 1952 by its dedicatee the great Rostropovich, the incredibly technically-challenging Symphonie Concertante for Cello, Op. 125 by Prokofiev was later reworked by the composer to give the orchestra a richer and more substantial role. The three movement work later inspired Shostakovich to write his first cello concerto, also dedicated to Rostropovich
Keywords: Cello; Concertos (Cello); Cello -- Instruction and study; Cello -- Performance; Cello music -- Interpretation (Phrasing, dynamics, etc.); Concertos (Cello) -- Excerpts -- Solo with piano; Documentary films; Internet videos